USING DIVERGENT AND CONVERGENT QUESTIONS IN DEVELOPING CREATIVE THINKING OF IRAQI EFL PREPARATORY STUDENTS' PERFORMANCE IN WRITING SKILL - Chilap, Hawazen Rasim; Dehham, Sabeeha Hamza; Akber, Nadia Ali (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at investigating whether or not there was a significant difference in writing achievement between the students who were taught by using divergent and convergent Questions technique and that of those who were not. The experimental method was conducted toward the fourth-grade students in Asmaa Bent Amaise High School in Najaf city in which sixty-five students were involved as the sample which was divided into two groups. In collecting the data, a written test was administered. Before giving the test, the test was tried out to non-sample students to know its validity and reliability. Then, the data were analyzed using a t-test. Building upon the results of the study, it has been figured out that there is a significant difference between the experimental and the control groups. Concerning the post-test, the mean score of the experimental group is (38.00), whereas that of the control group is (22.75). This signifies that the students’ achievement of the experimental group is significantly better than that of the control group.